Local (Agro) Ecological Knowledge of Jangkat (A note from the field) - Hariyadi, Bambang (Biospecies, 2009)
Jangkat is an indigenous group who inhabits a region bordering with the Kerinci SeblatNational Park. The group still strongly attaches with their tradition and implements traditional valuesin their daily lives. The Jangkat have developed local ecological knowledge by observing localecological dynamics intensely over generations. The knowledge is implemented in local agriculturalpractices that fit with local socio-cultural and natural condition. Latter on, the agro-ecologicalknowledge is incorporates into local customary institution (adat) and comes out with a sustainablenatural resource management model and improves the lives of the Jangkat people.